When should patients presenting with CVA receive thrombolytic agents?. Issue 10 (October 2017) - Okonkwo, Nzube; Madlon‐Kay, Diane
Abstract : EVIDENCE‐BASED ANSWER : Thrombolytic therapy improves the outcomes of neurological deficits in patients presenting with an ischemic stroke when given within 3 to 4.5 hours of symptom onset. Patients do not benefit from thrombolytic agents given later (SOR: A, meta‐analysis).